Reviewing Manuscripts Reporting Findings From Single-Case Research Design Studies. (February 2023) - Hott, Brittany L.; Flores, Margaret M.; Morano, Stephanie; Randolph, Kathleen M.; Peltier, Corey
This article, part of the Learning Disability Quarterly special series dedicated to single-case research design (SCRD), summarizes the review process and outlines how to provide high-quality SCRD study manuscript reviews. We offer recommendations for the entirety of the review process, including accepting the role of reviewer, evaluating quality of SCRD studies, and, finally, adhering to reporting standards with focused attention on the applied nature of the engaging work that encompasses research in learning disabilities. In addition, we discuss (a) participant and setting description, (b) implementation of particular designs, (c) measurement procedures for dependent variable(s), (d) providing evidence of reliability, (e) graphic display of time-series data, (f) descriptions of results, and (g) acknowledgment of design limitations. We describe the challenges facing SCRD researchers and reviewers engaging in learning disabilities research within applied settings, identify fatal flaws that authors cannot address, and point out omissions that researchers can address through the revision process. Implications for practice, resources, and future directions are shared.